2023
DOI: 10.3390/molecules28030936
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of Spores on Model Stainless-Steel Surface by Using Foams Based on Alkyl Polyglucosides

Abstract: In the food industry, the surfaces of processing equipment are considered to be major factors in the risk of food contamination. The cleaning process of solid surfaces is essential, but it requires a significant amount of water and chemicals. Herein, we report the use of foam flows based on alkyl polyglucosides (APGs) to remove spores of Bacillus subtilis on stainless-steel surfaces as the model-contaminated surface. Sodium dodecyl sulfate (SDS) was also studied as an anionic surfactant. Foams were characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Then, the stainless-steel plates were removed, and the effect of contact with the foam was quantified by measuring the spore log reduction after 30 min, as shown in Figure 5a. The spores' log reduction was around 1.13 ± 0.14 for the water due to the hydrophilicity of the spores, as already observed previously, which could be removed by water [29]. The spores' log reduction for the pure 10-HSA dispersion was 0.92 ± 0.20, which was similar to water.…”
Section: Cleaning Of Spore Contamination On Surfaces By Foam Imbibitionsupporting
confidence: 83%
See 2 more Smart Citations
“…Then, the stainless-steel plates were removed, and the effect of contact with the foam was quantified by measuring the spore log reduction after 30 min, as shown in Figure 5a. The spores' log reduction was around 1.13 ± 0.14 for the water due to the hydrophilicity of the spores, as already observed previously, which could be removed by water [29]. The spores' log reduction for the pure 10-HSA dispersion was 0.92 ± 0.20, which was similar to water.…”
Section: Cleaning Of Spore Contamination On Surfaces By Foam Imbibitionsupporting
confidence: 83%
“…In our case, we assume that even if the average liquid fractions were different, they were still within the range of wet foams, and we also assume that only the bubble size had an effect on foam imbibition [32]. Moreover, by comparing the log reduction obtained for the DS foam to the log reduction obtained for foam flow in dynamic conditions using the same spore model and the same surface, we observed that the values are similar, showing that foams in static conditions are very effective for efficiently removing spore contamination, thanks to the imbibition process [29].…”
Section: Cleaning Of Spore Contamination On Surfaces By Foam Imbibitionsupporting
confidence: 52%
See 1 more Smart Citation
“…Notably, immersing the contaminated surfaces in biosurfactant alone did not have any effect on cleaning. Furthermore, recent experiments with foam flows based on alkyl polyglucosides have shown promising results in efficiently removing spores from surfaces while minimizing the environmental impact (Dari et al, 2023). The combination of the mechanical effect of air–liquid interfaces and the chemical effect of biosurfactants presents an alternative cleaning procedure that could further enhance cleaning efficiency and decrease environmental impact.…”
Section: Cleaning Methodsmentioning
confidence: 99%
“…Alkyl polyglucoside (APG) is one of the well-known families of natural surfactants, derived from natural glucose and a fatty alcohol. It is considered as non-toxic, mild and environmentally friendly emulsifier (Dari et al, 2023). Our aim here was to study the stabilization of W/W emulsions by using LGNs based on various APGs.…”
Section: Introductionmentioning
confidence: 99%